128k views
1 vote
Can you explain to me in steps how to work this problem
4(2x-2)-4=4(x-5)+32

User MPPNBD
by
7.1k points

2 Answers

4 votes
4(2x - 2) - 4 = 4(x - 5) + 32
4(2x) - 4(2) - 4 = 4(x) - 4(5) + 32
8x - 8 - 4 = 4x - 20 + 32
8x - 12 = 4x + 12
-4x -4x
4x - 12 = 12
+12 +12
4x = 24
4 4
x = 6
User JDunkerley
by
7.4k points
6 votes

4\left( 2x-2 \right) -4=4\left( x-5 \right) +32\\ \\ 8x-8-4=4x-20+32\\ \\ 8x-12=4x+12


\\ \\ 8x-4x=12+12\\ \\ 4x=24\\ \\ \frac { 1 }{ 4 } \cdot 4x=\frac { 1 }{ 4 } \cdot 24\\ \\ x=6
User Utsav Parikh
by
7.7k points